Upaya Meningkatkan Mutu Pembelajaran PAI Melalui Pembelajaran Berbasis Digital (Studi Eksploratif di SMA Negeri 15 dan SMA Alfa Centauri Kota Bandung) - Iqbal Syahrijar; Udin Supriadi; Agus Fakhruddin (Departement of Mathematics Education, 2023)
This study aims to investigate digital-based learning as an effort to improve the quality of PAI learning. The research method used is a qualitative approach with the type of exploratory study to reveal contemporary phenomena which are then explored and identified. The data collected comes from primary data through interviews and observations at SMA Negeri 15 and SMA Alfa Centauri Bandung. The results of this study indicate that digital-based learning infrastructure in supporting PAI learning in schools consists of wifi, a set of computers or laptops, interactive screens, and CCTV. While the PAI learning process can be carried out digitally in classrooms and computer laboratories starting from planning, implementing, and evaluating. This research has implications for the importance of using information technology to improve the quality of Islamic religious education learning.